Kebijakan Perubahan Iklim Di Papua: Kolaborasi Antara Pemerintah Dan Masyarakat Adat - Wijaya, Nasri; Rahail, Emiliana B.; Jaya, Andi Ervin Novara (Jurnal Restorative Justice, 2025)
Papua, with Indonesia's richest biodiversity, faces significant climate change challenges. Sustainable policies require synergy among stakeholders, including indigenous communities with their local knowledge and traditional practices. The forest, seen as "Mama" by Papuans, is crucial for their livelihood and customs. Despite their efforts to protect it, indigenous communities remain vulnerable to climate impacts. Their limited participation in planning and decision-making often leads to ineffective climate solutions. This research explores policies by regional and central governments and the active role of indigenous communities, focusing on climate change due to the conversion of customary forests into oil palm plantations and the marginalization of indigenous communities from losing their ancestral forest rights and access. The qualitative study shows that collaboration between the government and indigenous communities can enhance climate policy effectiveness. Indigenous participation enriches local knowledge and strengthens environmental commitments. The article highlights partnership challenges, such as differing perspectives and the need for flexible policy adaptation. The main recommendations are to strengthen communication and build capacity at both government and indigenous community levels for effective climate change mitigation in Papua. This collaboration could serve as a model for other regions facing similar challenges.